A Strategic Approach to Regulating Unacceptable Forms of Work. (28th February 2019) - McCann, Deirdre; Fudge, Judy
Abstract : Upgrading low‐waged and insecure work is central to contemporary labour and development initiatives, from the UN Sustainable Development Goals to the United Kingdom 'Taylor Review'. The International Labour Organization's notion of unacceptable forms of work (UFW) is a crucial contribution. Yet the regulatory frameworks that can effectively address UFW are unclear. This article builds on a novel framework ‐ the Multidimensional Model of UFW. Drawing on theoretical literatures at the frontline of regulation scholarship, it proposes a strategic approach to UFW regulation that supports development, acknowledges the constrained resources of low‐income countries, and targets expansive and sustainable effects. Two key concepts are identified: points of leverage and institutional dynamism. Globally‐prominent regulatory frameworks are assessed as a starting point for mapping the strategic approach: the Mathadi Act of Maharashtra, India; Uruguayan domestic work legislation; minimum wages in the global North and South; and United Kingdom regulation of 'zero‐hours contracts'.